2023
DOI: 10.3390/genes14091732
|View full text |Cite
|
Sign up to set email alerts
|

Maize OPR2 and LOX10 Mediate Defense against Fall Armyworm and Western Corn Rootworm by Tissue-Specific Regulation of Jasmonic Acid and Ketol Metabolism

Pei-Cheng Huang,
John M. Grunseich,
Katherine M. Berg-Falloure
et al.

Abstract: Foliage-feeding fall armyworm (FAW; Spodoptera frugiperda) and root-feeding western corn rootworm (WCR; Diabrotica virgifera virgifera) are maize (Zea mays L.) pests that cause significant yield losses. Jasmonic acid (JA) plays a pivotal defense role against insects. 12-oxo-phytodienoic acid (12-OPDA) is converted into JA by peroxisome-localized OPDA reductases (OPR). However, little is known about the physiological functions of cytoplasmic OPRs. Here, we show that disruption of ZmOPR2 reduced wound-induced JA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…In these hormone related genes, some have been characterized functionally in maize growth or stress response. For instance, JA related genes, ZmLOX10 and ZmJAZ9 were involved in insect resistance, and ZmJAZ8 played roles in defense to C. graminicola infection [ 31 , 35 , 36 ]. Auxin biosynthesis genes, ZmYucca6 and ZmYucca9 were reported to participate into root geotropism and lodging resistance [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In these hormone related genes, some have been characterized functionally in maize growth or stress response. For instance, JA related genes, ZmLOX10 and ZmJAZ9 were involved in insect resistance, and ZmJAZ8 played roles in defense to C. graminicola infection [ 31 , 35 , 36 ]. Auxin biosynthesis genes, ZmYucca6 and ZmYucca9 were reported to participate into root geotropism and lodging resistance [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we showed that T. virens colonization significantly enhanced mortality and suppressed weight gain of WCR larvae. Our previous report showed that increased WCR mortality was correlated with greater levels of herbivory-induced production of insecticidal death acids and ketols [16]. Therefore, one of the potential mechanisms of T. virens-mediated WCR defense may be to activate the production of insecticidal defensive compounds.…”
Section: Discussionmentioning
confidence: 98%
“…The laboratory strain of fall armyworm (FAW; Spodoptera frugiperda) was purchased from Benzon Research (Carlisle, PA, USA). Two weeks after incubation with the beneficial microorganisms, six FAW neonates were placed to the whorls of maize seedlings contained in individual plastic jars and allowed to move and feed on the plants freely for 7 days, as described in Huang et al (2023b) [16]. FAW larvae were removed from the plants, and the total weight was determined 7 days post-infestation.…”
Section: Fall Armyworm Assaymentioning
confidence: 99%
See 2 more Smart Citations